Multiculturalism in the Islamic Texts View and its Relevance to Interreligious Harmony in Indonesia - Kasdi, Abdurrohman; Farida, Umma (FIKRAH, 2019)
The study describes the concept of multiculturalism and its relevance to realizing the religious harmonization in Indonesia. Quran and hadith are the main source of Islamic text. The data gain through documentation. The obtained data analyzed critically-descriptive. The study reveals the ethnic and religious plurality is the empirical fact that Indonesia has been destined. Indonesia is a nation consisting of various tribes, customs, cultures, and religions. The study shows that multiculturalism in the view of Islamic texts has the relevance of the meaning and function that is appropriate to be developed and internalized in the process of transforming the values of the diverse communities and peoples of Indonesia.